Pengaruh Perlakuan Panas Terhadap Struktur Mikro, Kekerasan dan Ketahanan Oksidasi Suhu Tinggi Pada Baja Tahan Karat Martensitik 13Cr3Mo3Ni-Cor - Moch Syaiful Anwar; Eric Jonathan Yulianto; Septian Adi Chandra; Rahma Nisa Hakim; Sri Hastuty; Efendi Mabruri (Diponegoro University, 2019)
This paper reports the effect of heat treatment on microstructure, hardness and high-temperature oxidation resistance of martensitic stainless steels13Cr3Mo3Ni-cast. The aim of this reseach is to increase quality of the steel through heat treatment process on microstructure, hardness and high-temperature oxidation resistance. The steels samples were prepared by a process sequence ofinduction melting, casting, austenitisazed, single tempered and double tempered. Austenitization process of 1020°C was conducted until 4 hours and quench in water. Then, tempering process of 650°C was carried out until 2 hours and cooled in the air and then double tempering process of 550°C was carried out until 2 hours and air cooled. The double tempered steels were subjected to microstructure, hardness and high-temperature oxidation test of 400 – 700 °C. Then, the experimental results of double tempered steel were compared with control, austenitisazed and single tempered steels. The double tempered treatment revealed a positive effect on the increament properties of martensitic stainless steel 13Cr3Mo3Ni-cast in the high-temperature environment.